Intreractional Linguistics - Couper-Kuhlen, Elizabeth; Selting, Margret (United Kingdom: Cambridge University Press, 2018)
The first book dedicated to interactional linguistics, focusing on linguistic analyses of conversational phenomena, the introduction provides an overview of the theory and methodology of interactional linguistics.
Includes Bibliographic references and index.
Keywords: Discourse analysis-Social aspects--Conversation analysis--Intercultural communication--Pragmatics